On women and ethics: Julia Kristeva’s "difference" - Carbonell, Neus (Tropelías: Review of Literary Theory and Comparative Literature, 1995)
"On women and ethics: Julia Kristeva’s difference" reads those texts by the writer, literary critic and psychoanalist Julia Kristeva which analize the problem of female subjectivity and its cultural construction. Taking as point of departure the following works: Révolution du language poétique (1974), Des Chinoises (1974), Histories d’amour (1983) y "Women’s Time" (1979), the ideas of the author concerning the subject of enuntiation, the feminine, the maternal and sexual difference are analized. This article’s thesis contends that, contrary to other postmodern practices, Kristeva’s theories can be seen as a response to the obliteration of woman and women, as subjects and as group, in history. Hence, positioning herself in a (male) tradition of knowledge and thought, Julia Kristeva has explored ways of trascending this tradition in order to create a discourse of and for women.